2012
DOI: 10.3168/jds.2011-4840
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of potassium carbonate sesquihydrate to increase dietary cation-anion difference in early lactation cows

Abstract: The effect of additional dietary potassium in early lactation dairy cows was evaluated with the addition of potassium carbonate sesquihydrate, which increased dietary K from 1.3 to 2.1% of dry matter (DM) from wk 3 to 12 of lactation. Cows fed potassium carbonate sesquihydrate in the form of DCAD Plus (Church & Dwight Co. Inc., Princeton, NJ) had increased DM intake, milk fat percentage and yield, energy-corrected milk, and efficiency of milk production per unit of DM intake. Milk fat of cows fed higher dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…For example, Harrison et al (2012) reported that FE improved by 0.11 units when DCAD was increased from 490 to 700 mEq/kg of DM with added dietary K as the cation source. Erdman et al (2011) reported a 0.14-unit increase in FE by increasing DCAD in a corn silage-based diet from 255 to 336 mEq/kg of DM with added K 2 CO 3.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…For example, Harrison et al (2012) reported that FE improved by 0.11 units when DCAD was increased from 490 to 700 mEq/kg of DM with added dietary K as the cation source. Erdman et al (2011) reported a 0.14-unit increase in FE by increasing DCAD in a corn silage-based diet from 255 to 336 mEq/kg of DM with added K 2 CO 3.…”
Section: Discussionmentioning
confidence: 97%
“…In the present studies, dietary treatments were applied in 3-wk experimental periods, which are probably sufficient to allow for changes in milk fat percentage to be expressed (Rico and Harvatine, 2013) but insufficient to measure the full magnitude of milk production and DMI effects. In the studies of Erdman et al (2011) and Harrison et al (2012), treatments were applied at the beginning of lactation and lasted for 140 and 70 d, respectively. Thus, under commercial conditions, the expected FE response to DCAD would be expected to be greater when dietary changes in DCAD are applied at the herd level and maintained continuously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations